Analisis Perasaan Cinta Edward Cullen terhadap Bella Swan dalam Midnight Sun Karya Stephenie Meyer - Khersy Runtuwene; Dewi Christa Kobis; Muh. Hasan Basri (CV Edujavare Publishing, 2026)
Midnight Sun is a novel by Stephenie Meyer published 2020. The novel has one main character, Edward Cullen, and several supporting characters, including Bella Swan, Alice Cullen, and Carlisle Cullen. Love Felling is the main theme in the novel. The purpose of this study is to find out what is the factor that makes his love felling grow for Bella Swan and. This study used a descriptive research. This study used based on Wellek and Warren’s intrinsict approach. This study used Robert Sternberg's Triangular Theory of Love posits that love is composed of three essential components: intimacy, passion, and commitment. These components interact in different combinations to form various types of love, ranging from non-love (the absence of all three) to consummate love (a balanced combination of all three). The theory suggests that the relative importance of these components can change over time, and that relationship success is linked to compatibility between partners'